Latrogenic hypospadias-a preventable rare complication with two-stage repair with Buccal Mucosa Graft: a case presentation - Yusof, M. R.; Mohd Sharin, M. F.; Aizat Sabri, I.; Jagwani, A. V.; Lee, F. Y.; Ahmad Zaidi, A. I.; Saiful Azli, M. Z.; Rishitra, R. K.; Fahmey, O.; Lee, C. K. S.; Khairul-Asri, M. G. (Russian Society Urology, 2023)
Urethral catheterization is a common procedure, but it is associated with a number of complications. Iatrogenic hypospadias can rarely occur. There is a limited literature dedicated to this condition. We report a young patient with COVID-19 with iatrogenic hypospadias of grade 3. He was undergone to a two-stage procedure with acceptable outcome. Surgical repair should be offered and performed for young patients to ensure good function with acceptable penile appearance. A surgical treatment will improve psychological, sexual and social outcomes.